2001
DOI: 10.1002/ana.1130
|View full text |Cite
|
Sign up to set email alerts
|

Low cerebrospinal fluid hypocretin (orexin) and altered energy homeostasis in human narcolepsy

Abstract: Hypocretins (orexins) are hypothalamic neuropeptides involved in sleep and energy homeostasis. Hypocretin mutations produce narcolepsy in animal models. In humans, narcolepsy is rarely due to hypocretin mutations, but this system is deficient in the cerebrospinal fluid (CSF) and brain of a small number of patients. A recent study also indicates increased body mass index (BMI) in narcolepsy. The sensitivity of low CSF hypocretin was examined in 38 successive narcolepsy-cataplexy cases [36 human leukocyte antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
207
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 416 publications
(223 citation statements)
references
References 31 publications
9
207
2
5
Order By: Relevance
“…Cerebrospinal fluid levels of hypocretin-1 were measured using RIA kits (Phoenix Pharmaceuticals, Mountain View, CA, USA) as reported elsewhere. 1 As the method for measuring hypocretin-2 is not yet established, it was not studied. Statistical analysis was made using one-way ANOVA and Fisher's least significant difference test (PLSD), and Fisher's exact probability test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebrospinal fluid levels of hypocretin-1 were measured using RIA kits (Phoenix Pharmaceuticals, Mountain View, CA, USA) as reported elsewhere. 1 As the method for measuring hypocretin-2 is not yet established, it was not studied. Statistical analysis was made using one-way ANOVA and Fisher's least significant difference test (PLSD), and Fisher's exact probability test.…”
Section: Methodsmentioning
confidence: 99%
“…1 These peptides have aroused interest in light of two recent reports linking dysfunction of the hypocretin peptide-receptor system to animal models of narcolepsy. In 2000, Nishino et al reported that hypocretin-1 in the cerebrospinal fluid (CSF) was significantly lower in patients with narcolepsy compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocretin peptides were originally described as modulators of food intake, with central administration of hypocretin enhancing food intake in rodents 25. Despite this observation, body mass indices have been found to be increased rather than decreased in narcoleptic humans, with the most marked increases in body mass indices seen in those with undetectable CSF hypocretin levels 25, 26. Also, hypocretin deficiency might not be as important as deficiencies of other neuropeptides that are colocalized in neurons that produce hypocretin.…”
mentioning
confidence: 99%
“…Orexin deficiency has been shown to be involved in the pathogenesis of narcolepsy in human and animal models, such as mice with knockout mutations in the gene for prepro-orexin (prepro-orexin knockout mice, referred to throughout the remainder of this article as orexin knockout mice) and orexin neuron-deficient mice [10,11]. In humans, narcolepsy is accompanied by energy imbalance, such as decreased energy intake and increased BMI, resulting in an increase in the incidence of type 2 diabetes [12][13][14][15]. Mice deficient in orexin neurons also exhibit late-onset obesity, despite eating less [16], and on a high-fat diet, become heavier than wildtype mice [17].…”
mentioning
confidence: 99%